2020
DOI: 10.3390/molecules25102302
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Thiosemicarbazides with Clinical Drugs against S. aureus

Abstract: Antimicrobial resistance spurred by the overuse and misuse of antibiotics is a major global health concern, and of the Gram positive bacteria, S. aureus is a leading cause of mortality and morbidity. Alternative strategies to treat S. aureus infections, such as combination therapy, are urgently needed. In this study, a checkerboard method was used to evaluate synergistic interactions between nine thiosemicarbazides (4-benzoyl-1-(2,3-dichloro-benzoyl)thiosemicarbazides 1–5 and 4-aryl-1-(2-fluorobenzoyl)thiosemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Taking this fact into account, the results of the MBC assay are not surprising. In fact, in our previous studies [ 23 ], on the thiosemicarbazides 9a and 10a, we showed that their inhibitory action against S. aureus DNA gyrase was very weak; compound 10a was able to inhibit ~50% of S. aureus DNA gyrase activity at as high a concentration as 100 µg/mL, whereas the inhibitory activity of 9a at this concentration was even lower (~33%). Collectively, the results of the MBC assay further confirm the assumption that, for our bacteriostatic thiosemicarbazides of sets I – III, bacterial topoisomerases are not primary factors contributing to their antibacterial activity.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Taking this fact into account, the results of the MBC assay are not surprising. In fact, in our previous studies [ 23 ], on the thiosemicarbazides 9a and 10a, we showed that their inhibitory action against S. aureus DNA gyrase was very weak; compound 10a was able to inhibit ~50% of S. aureus DNA gyrase activity at as high a concentration as 100 µg/mL, whereas the inhibitory activity of 9a at this concentration was even lower (~33%). Collectively, the results of the MBC assay further confirm the assumption that, for our bacteriostatic thiosemicarbazides of sets I – III, bacterial topoisomerases are not primary factors contributing to their antibacterial activity.…”
Section: Resultsmentioning
confidence: 91%
“…The synthesis of ortho -, meta -, and para -fluorobenzoylthiosemicarbazides (sets I – III ) and their cyclic analogues with a 1,2,4-triazole-5-thione scaffold (sets IV – VI ) was performed according to a well-established synthetic route, described elsewhere [ 23 , 34 ] ( Scheme 1 ). The reaction of the corresponding fluorobenzoylhydrazide with related alkyl/aryl isothiocyanate in boiling ethanol gave 1-fluorobenzoyl-4-aryl/(alkyl)thiosemicarbazides (sets I – III ) in 40–90% yields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, thiosemicarbazide derivatives are biologically active, noncytotoxic organic compounds with proven antitumor, antiviral, antifungal, and antioxidant activities [ 27 , 28 , 29 , 30 , 31 , 32 ] but are also precursors for thiosemicarbazones, which are formed by the condensation of thiosemicarbazide or substituted thiosemicarbazide at the N4 position with a suitable aldehyde or ketone [ 33 ]. Last, thiosemicarbazone derivatives were described as anti-inflammatory factors, especially in the inflammatory response mediated by nuclear factor kappa light-chain-enhancer of activated B cells (NF-κB), by inhibiting NF-κB transactivation [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thiosemicarbazides are biologically active, noncytotoxic organic compounds with proven antitumor, antiviral, antifungal, and antioxidant activities. Furthermore, the strong antibacterial potential of various thiosemicarbazide derivatives has also been documented [ 6 , 7 , 8 , 9 , 10 ]. Although the in vitro activity of imidazolo-thiosemicarbazide against the virulent Mtb H37Rv strain has not previously been described, other than in the present study, many derivatives containing thiosemicarbazide moieties have been synthesized and evaluated for their antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%